2006
DOI: 10.1111/j.1708-8208.2006.00011.x
|View full text |Cite
|
Sign up to set email alerts
|

Syncrystallization: A Technique for Temporization of Immediately Loaded Implants with Metal‐Reinforced Acrylic Resin Restorations

Abstract: The results of this study indicate that the syncrystallization technique allows an expedite and adequate rigid splinting of multiple immediately loaded implants. The advantages of the technique are: (1) reduction of treatment time for immediate temporization at stage 1 surgery; (2) predictable fixation and immobility of implants in the early stages of bone healing; and (3) less time for repairing provisional restorations as a result of no or rare fracture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
61
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(67 citation statements)
references
References 40 publications
0
61
0
Order By: Relevance
“…In recent years, several clinical studies have reported excellent results obtained using intraoral welding techniques for the rehabilitation of completely edentulous mandibles with screw-retained full arch immediately loaded prostheses and Toronto bridges [2][3][4][5][6]. Similar results have also been reported for procedures on the fully edentulous maxilla [6,18,19], giving the impression that intraoral welding can be successfully used for the rehabilitation of edentulous patients.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…In recent years, several clinical studies have reported excellent results obtained using intraoral welding techniques for the rehabilitation of completely edentulous mandibles with screw-retained full arch immediately loaded prostheses and Toronto bridges [2][3][4][5][6]. Similar results have also been reported for procedures on the fully edentulous maxilla [6,18,19], giving the impression that intraoral welding can be successfully used for the rehabilitation of edentulous patients.…”
Section: Discussionmentioning
confidence: 67%
“…One of the obvious advantages of the intraoral welding technique is the ability to rehabilitate in a very short timeframe and with limited costs fully edentulous patients, without going through lengthy and complex laboratory phases [2][3][4][5][6]18]. Recently, some potential alternatives to the traditional technique originally proposed by P. L. Mondani and P. M. Mondani [1] and subsequently recovered by Degidi et al [3,5,6,18] have been proposed [7,8]. Albiero and Benato [8] published a case report in which the technique of intraoral welding has been combined with modern guided surgical techniques.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4][5][6][7][8][9][10][11][12] For this purpose, the most frequently used methods are the production of a cast bar to be fastened to the implants with screws or with the placement of a metal reinforced screwed/cemented temporary prosthesis. [13][14][15][16][17][18][19][20][21][22][23][24][25] An interesting alternative is given by the intraoral welder.…”
Section: Introductionmentioning
confidence: 99%